2003
DOI: 10.1021/es034151o
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Sediment-Associated PCDD/Fs and PCDEs:  Relative Importance of Contaminant and Sediment Characteristics and Biological Factors

Abstract: Factors that determine accumulation of sediment-associated polychlorinated dibenzo-p-dioxins and furans and polychlorinated diphenyl ethers into semipermeable membrane devices (SPMDs) and benthic oligochaete worms (Lumbriculus variegatus) were examined. These factors included both physical-chemical and structural characteristics of the contaminants (water solubility, lipophilicity, dipole moment, molecular size, and conformation) and sediment characteristics (organic carbon content, particle size, aromaticity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 52 publications
(76 reference statements)
4
43
0
Order By: Relevance
“…After removing the inorganic carbon with 1 mol/L HCl, the sediments were heated at 60 C until dry or at 450 C for 4 h, and used for the OC or BC analysis, respectively. Sediment aromaticity and planarity were calculated using the ratios of hydrogen/ carbon and carbon/nitrogen, respectively (Lyytikainen et al, 2003). Finally, the sediment grain size distribution was determined by wet sieving the samples sequentially through three sieves (830 mm, 180 mm and 58 mm).…”
Section: Sediment Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After removing the inorganic carbon with 1 mol/L HCl, the sediments were heated at 60 C until dry or at 450 C for 4 h, and used for the OC or BC analysis, respectively. Sediment aromaticity and planarity were calculated using the ratios of hydrogen/ carbon and carbon/nitrogen, respectively (Lyytikainen et al, 2003). Finally, the sediment grain size distribution was determined by wet sieving the samples sequentially through three sieves (830 mm, 180 mm and 58 mm).…”
Section: Sediment Collection and Analysismentioning
confidence: 99%
“…One of the reasons for this discrepancy is that contaminants have distinct sorption capacities to different types of OC, but the understanding of OC classification and the partitioning processes of contaminants within OC is still quite limited . In addition, other factors may also affect bioavailability and toxicity of sediment-associated contaminants, including sediment grain size (Mehler et al, 2011b), sediment aromaticity and planarity (Lyytikainen et al, 2003), niches of the test organisms (Wang et al, 2004), and chemical properties (You et al, 2007). Thus, it is beneficial to incorporate bioavailability measurements into risk assessments to improve the accuracy of sediment toxicity estimates .…”
Section: Introductionmentioning
confidence: 99%
“…Vlčková and Hofman (2012) also observed a reduced bioaccumulation in earthworms with aging for PAHs as well as chlorinated compounds (e.g., CB-153) in both natural and artificial soils. Compared with PCBs, PCDD/Fs have been proven to be more strongly adsorbed to organic carbon, making them less bioavailable (Lyytikäinen et al, 2003), which could be the most likely explanation for the generally lower BSAFs for PCDD/Fs. On the other hand, the relatively larger molecular size of some of these halogenated compounds can restrict the membrane permeation potential and limit the uptake by earthworm, which could also lead to lower BSAF values for the higher-halogenated congeners.…”
Section: Bioaccumulation In Earthwormmentioning
confidence: 99%
“…4A), only a slight downtrend was observed (linear regression R 2 = 0.25, p = 0.04), which is consistent with our previous observation ) and the investigation by Nakamura et al (2007) and Fagervold et al (2010), but less comparable to the study by Matscheko et al (2002) that reported an evidently decreasing trend with increasing hydrophobicity of PCDD/Fs. PCDD/Fs are proven to be more strongly adsorbed to organic carbon, making them less bioavailable (Lyytikäinen et al, 2003). These higher K ow compounds also tend to have large molecular sizes that can reduce their potential to penetrate biological membranes and decrease the bioavailability in earthworm, which could also result in lower BSAFs and decreasing trend with increasing log K ow .…”
Section: Bioaccumulation In Earthwormmentioning
confidence: 99%
“…BAF, defined as the ratio between the PCDD/Fs concentration in earthworm and PCDD/Fs concentration in the soil was calculated as (Lyytikäinen et al, 2003):…”
Section: Bioaccumulation Factor (Baf)mentioning
confidence: 99%